The potential and current applications of tapioca (Manihot esculenta crantz) flour and starch as functional ingredients in food products – a review - Macdalyna Esther Ronie; Hasmadi Mamat; Ahmad Hazim Abdul Aziz; Norazlina Mohammad Ridhwan; Rovina Kobun; Wolyna Pindi; Mohamad Khairi Zainol; Nicky Rahmana Putra (Faculty of Food Science and Nutrition, UMS, 2025)
Tapioca, derived from the cassava plant (Manihot esculenta Crantz), stands as a versatile and significant starch source globally. Tapioca flour and tapioca starch present numerous promising opportunities for future applications in the food industry. The review explores tapioca's scientific foundations, examining its chemical composition and potential application in food products. Extensive research showcases tapioca flour's effectiveness as a gluten-free alternative, enhancing texture, moisture retention, and overall quality in gluten-free products. Tapioca's contributions to texture modification in food products, along with its remarkable thickening properties underscore its versatility in diverse food applications. Tapioca's remarkable versatility enhances its reputation as a food ingredient by consistently improving the quality of food products. Additionally, innovations in gluten-free food products using tapioca flour can cater to those with gluten intolerance or celiac disease, offering more diverse and nutritious options. In conclusion, while tapioca flour holds significant promise for future applications in the food industry, overcoming these challenges through research, innovation, and strategic planning will be essential for its successful integration into diverse food products.